Association of the Robert Wood Johnson Foundations' social determinants of health and Medicare hospitalisations for ischaemic strokes: a cross-sectional data analysis. Issue 1 (8th January 2020) - Wang, Andrew; Kho, Abel N; French, Dustin D
Abstract : Objective: Social determinants of health (SDH) have previously demonstrated to be important risk factors in determining health outcomes. To document whether the SDH are associated with hospitalisations for ischaemic stroke. Methods: This cross-sectional study examines data from fiscal year 2015. Patients from the national Medicare 100% Inpatient Limited Dataset were linked with SDH measures from the Robert Wood Johnson Foundation (RWJF) County Health Rankings. Medicare patients were included in the study group if they had either an admitting or primary diagnosis of ischaemic stroke. Counties without RWJF data were excluded from the study. Ischaemic strokes were compared with all other hospitalisations associated with characteristics of the SDH measures and benchmarked to above or below their respective national median. Estimates were performed with nested logistic regression. Results: Approximately 256 766 Medicare patients had ischaemic stroke hospitalisations compared with all other Medicare patients (n=6 386 180) without ischaemic stroke hospitalisations while 30 853 patients were excluded due to residence in US territories. Significant factors included air pollution exceeding the national median (OR 1.06; 95% CI 1.05 to 1.07), per cent of children in single parent households exceeding the national median, (OR 1.02; 95% CI 1.01 to 1.03), violent crime rates exceeding the national median, (OR 1.02; 95% CI 1.01 to 1.03) and per cent smoking exceeding the national median, (OR 1.02; 95% CI 1.01 to 1.03). Conclusions: When cross-sectional SDH are benchmarked to national median for ischaemic stroke hospitalisations and compared with all-cause hospitalisations, the effects remain significant. Further research on the longitudinal effects of the SDH and cardiovascular health, particularly disease-specific outcomes, is needed.